Changes in Endoplasmic Reticulum Luminal Environment Affect Cell Sensitivity to Apoptosis - Nakamura, Kimitoshi (The Rockefeller University Press, 2000)
To test the role of ER luminal environment in apoptosis, we generated HeLa cell lines inducible with respect to calreticulin and calnexin and investigated their sensitivity to drug-dependent apoptosis. Overexpression of calreticulin, an ER luminal protein, resulted in an increased sensitivity of the cells to both thapsigargin- and staurosporine-induced apoptosis. This correlated with an increased release of cytochrome c from the mitochondria. Overexpression of calnexin, an integral ER membrane protein, had no significant effect on drug-induced apoptosis. In contrast, calreticulin-deficient cells were significantly resistant to apoptosis and this resistance correlated with a decreased release of cytochrome c from mitochondria and low levels of caspase 3 activity. This work indicates that changes in the lumen of the ER amplify the release of cytochrome c from mitochondria, and increase caspase activity, during drug-induced apoptosis. There may be communication between the ER and mitochondria, which may involve Ca(2+) and play an important role in conferring cell sensitivity to apoptosis. Apoptosis may depend on both the presence of external apoptosis-activating signals, and, as shown in this study, on an internal factor represented by the ER.